2013
DOI: 10.1128/aac.00796-13
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Zinc Acetate Gel, a Potential Nonantiretroviral Microbicide, Is Safe and Effective against Simian-Human Immunodeficiency Virus and Herpes Simplex Virus 2 Infection In Vivo

Abstract: We previously showed that a prototype gel comprising zinc acetate (ZA) in carrageenan (CG) protected mice against vaginal and rectal herpes simplex virus 2 (HSV-2) challenge as well as macaques against vaginal simian-human immunodeficiency virus reverse transcriptase (SHIV-RT) challenge. In this work, we modified buffers and cosolvents to obtain a stable, nearly iso-osmolal formulation and evaluated its safety and efficacy against SHIV-RT and HSV-2. In vitro toxicity to lactobacilli and Candida albicans was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
2
23
0
1
Order By: Relevance
“…CG gel does not damage vaginal or rectal epithelial tissue in mice. It does not increase susceptibility to HSV-2 vaginal infection in mice and is nontoxic to Lactobacillus jensenii or Lactobacillus crispatus in vitro (Kenney et al, 2013). Experiments in macaques show that repeated application is safe with no effects on vaginal pH or cytokines and chemokine levels in fluids (Kenney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CG gel does not damage vaginal or rectal epithelial tissue in mice. It does not increase susceptibility to HSV-2 vaginal infection in mice and is nontoxic to Lactobacillus jensenii or Lactobacillus crispatus in vitro (Kenney et al, 2013). Experiments in macaques show that repeated application is safe with no effects on vaginal pH or cytokines and chemokine levels in fluids (Kenney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the excellent safety profile, rheological properties, and anti-HPV activity of a 3% CG gel, we have used CG-based gels as delivery vehicles for anti-HIV and anti-HSV-2 APIs (Fernández-Romero et al, 2012; Kenney et al, 2011; Kenney et al, 2013; Kenney et al, 2012; Kizima et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The authors confirmed that the drug could block sexual transmission of the virus, exhibited low toxicity in vitro, caused minimal changes to the vaginal and rectal mucosa, without affecting functions of vaginal epithelial cells and normal vaginal flora. Later, the authors demonstrated the efficacy of the modified gel in experiments in vivo [77]. For example, gel protected 60% of animals from vaginal and 80% of animals from rectal infection with the high dose of HSV 2.…”
Section: Action Of Algal Sulfated Polysaccharides On Genital Herpesvimentioning
confidence: 96%
“…This latter compound has been demonstrated to be innocuous for the vaginal tissue and its microflora, as well as preserve its pH in the presence of seminal plasma. Another microbicide with potential is the combination of zinc acetate and carrageenin (AZ/CG) ( Table 2) [182]. AZ/CG decreases up to 80 % infection with HSV-2 in macaques, and its activity would be mediated by the binding of Zn to viral membrane glycoproteins impairing the entry of the virus into target cells [183].…”
Section: Microbicides/antivirals Assessed In Clinical Settingsmentioning
confidence: 99%